(untitled) (Research, Society and Development, 2022)
The use of enzymes as part of bioelectrodes in Biofuel Cells (BFC) has been studied more often every day, aiming to reduce the operational and manufacturing high costs due in part to the use of metallic conventional catalyst. The in-situ production of biocatalysts can reduce even further these costs. However, some biocatalysts need the supplementation of external electrochemical mediators to achieve good coulombic efficiencies when these are used attached to bioelectrodes. In this work, two filamentous fungi were isolated from the soil of the Brazilian Caatinga Biome, that showed high oxidase activity in media containing two synthetic electronic shuttles, compared with four natural fungal pigments. Parameters such as substrate consumption, oxidase activity and microbial growth were evaluated. As was observed, all natural mediator pigments induced the enzyme production, observing an increase on enzyme production of more than 50% especially in two of them.